Gaston Bachelard’s Pedagogical Theory of Literature - Caccia, Carlo Alessandro (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2023)
Gaston Bachelard’s role is underrated in the international canon of literary theory. His aesthetical works could be much more enhanced by outlining their pedagogical features. In this essay, we will attempt to enhance the usefulness of Bachelard’s educational model for teaching literature today, which will be further highlighted by comparing it with the pedagogical thinking conceptualized by contemporary American literary theorist David Bleich. In the first part of this essay, we will introduce the main concepts of Bachelard’s and Bleich’s educational theories and, in the second part, we will outline the points of affinity and divergence between them. After this comparison, Bachelard’s model of reading education seems to be more balanced because it establishes a balanced relationship between text and reader and enhances the active and spiritual role of teacher and student.